The Bipolar Prodrome Symptom Interview and Scale–Prospective (BPSS‐P): description and validation in a psychiatric sample and healthy controls. (8th May 2014) - Correll, Christoph U; Olvet, Doreen M; Auther, Andrea M; Hauser, Marta; Kishimoto, Taishiro; Carrión, Ricardo E; Snyder, Stephanie; Cornblatt, Barbara A
<x xml:space="preserve">Abstract</x> Objective The aim of the present study was to investigate the psychometric properties of the Bipolar Prodrome Symptom Interview and Scale–Prospective (BPSS‐P), the first specific interview for emerging bipolar disorder (BD) symptoms. Methods A total of 205 youth aged 12–23 years and/or their caregivers underwent BPSS‐P interviews: 129 patients with mood spectrum disorders [depression spectrum disorder (n = 77), mood disorder not otherwise specified (NOS) (n = 27), BD‐NOS (n = 14), bipolar I disorder (BD‐I)/bipolar II disorder (BD‐II)/cyclothymia (n = 11), 34 with non‐mood spectrum disorders, and 42 healthy controls (HCs)]. We used Cronbach's α to assess internal consistency; intra‐class correlation (ICC) for inter‐rater reliability; Spearman's rho for convergent validity with the Young Mania Rating Scale (YMRS), General Behavior Inventory–10‐item Mania Form (GBI‐M‐10), and Cyclothymic–Hypersensitive Temperament (CHT) scale; and analysis of variance for discriminatory power between diagnostic groups. Results Internal consistency was good to very good for the BPSS‐P Mania (Cronbach's α = 0.87), Depression (Cronbach's α = 0.89), and General Symptom indices (Cronbach's α = 0.74). Inter‐rater reliability was high for the BPSS‐P Total score (ICC = 0.939), and BPSS‐P Mania (ICC = 0.934), Depression (ICC = 0.985), and General (ICC = 0.981) indices. Convergent validity was large (ρ ≥ 0.50) between the BPSS‐P Mania Index and YMRS, GBI‐M‐10, and CHT; BPSS‐P Depression Index and Montgomery–Åsberg Depression Rating Scale (MADRS) and CHT; and BPSS‐P General Index and GBI‐M‐10 and CHT. Expectedly, convergent validity was small (ρ = 0.10 to < 0.30) between the BPSS‐P Mania Index and MADRS, and BPSS‐P Depression Index and YMRS. Furthermore, the BPSS‐P and its subscales discriminated each patient group from HCs and from non‐mood spectrum patients (except for the BPSS‐P General Index). Moreover, the BPSS‐P Total score discriminated BD‐I/BD‐II/cyclothymia from depression spectrum patients, and the BPSS‐Mania Index differentiated all three bipolar spectrum groups from depression spectrum patients. Conclusions The BPSS‐P has good to excellent psychometric properties. Its use across multiple settings and predictive validity requires further investigation.